Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) IX. The maculosa species-group, with descriptions of eighteen new species - Wang, Shuxia; Liu, Chen (Zootaxa, 2020)
The maculosa species-group of the genus Promalactis Meyrick, 1908 is proposed based on the features of the forewing pattern. Members of this group have a white speckle in the forewing cell and usually with more than eight white markings distributed mostly at or above the fold and along the dorsal margin. Eighteen new species are described: P. coloristigmosa sp. nov., P. cruciata sp. nov., P. lateridentalis sp. nov., P. latispinata sp. nov., P. lonchodes sp. nov., P. magnispina sp. nov., P. plicata sp. nov., P. bomiensis sp. nov., P. fasciserrata sp. nov., P. brevipalpa sp. nov., P. libona sp. nov., P. medilargissima sp. nov., P. ramivalvata sp. nov., P. aculeiformis sp. nov., P. apicitriangula sp. nov., P. curvispinosa sp. nov., P. medimacularis sp. nov., and P. serraticostalis sp. nov. Photographs of adults and genitalia of the new species are provided. A total of 50 species of the maculosa species-group are listed, including 32 previously known species.